Methods of evaluating adaptation and accuracy of additive manufactured removable partial dentures: a scoping review - Safa Elhadery,; Norlela Yacob,; Syarida Hasnur Safii,; Norliza Ibrahim,; Zubaidah Zanul Abidin,; Nosizana Mohd Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aimed to provide a comprehensive review of various recent methods that can be used to assess the fit and accuracy of additive-manufactured removable partial dentures (RPDs), focusing on 3D-printed RPDs. An electronic search of the English language literature from January 2000 to February 2022 was performed using four databases: Medline/PubMed, Scopus, Web of Science, and EBSCOhost, using relevant keywords. The parameters of interest were extracted and tabulated. Of 936 retrieved studies, 26 studies were included. Most of the studies were laboratory studies, conducted between 2011 and 2022, did not include control group, used stone cast model as reference, used direct 3D printing method, and polished the final RPD framework. Methods of assessment can be divided into two categories: 1) qualitative assessment which is based mainly on visual inspection or tactile sense, and 2) quantitative assessment which includes optical assessment (with or without a registration material) and computerized assessment based on surface-matching software programs. In conclusion, computerized assessment using different surface matching software provides more accurate and precise quantitative assessment of denture fit and allows researcher and practitioner to detect minute dimensional changes that cannot be detected visually.